Pengaruh Lingkungan Kerja, Kepribadian, Dan Komunikasi Interpersonal Terhadap Komitmen Organisasi Dosen Universitas Darma Persada Di Jakarta (2012) - Sunengsih, Nani Dewi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The aim of this research is to obtain information related to the effect of work environment, personality, and interpersonal communication on lecturers’ organizational commitment of Darma Persada University in Jakarta.